Staropolskie struktury i satyry menippejskie. Próba typologii gatunku - Kusiak, Jolanta (Przestrzenie Teorii, 2008)
In the article Old Polish satires and menippean structures. An attempt at a typology of the genre the author took up the subject of the possibility of existence of this kind of satire derived from the antique tradition. Thus, what needed to be more precisely explained was the incoherent theoretical classification of ancient menippean satires and their influence on the later texts. An attempt at ordering the hitherto statements on the subject by scholars (among other M. Bakhtin, N. Frye, D. Shanzer, H. Rikonnen, K. Korus, R. Piętka and J. Styka) was enriched with a not well known German studies, especially Stefan Trappen's important book. The outline of the background of antique tradition of the genre allowed a wider view at the 17th and 18th century texts (old Polish texts) amongst which menippean satires can be found. On the grounds of native history of literature a division appeared to be indispensable into texts which either formally or actually belong to this genre, thus to the menippean structures and satires. The form of prosimetrum which characterises, among other things, Cadka Hrycia z Fortuną [Hryd's chat with Fortune] by J.S. Herburt or Something New... by Ł. Opaliński does not necessarily become the only constitutive genological feature of mennipea. Tracking the presence of the menippean satire in old literature ended with the observation of 4 important works: Żona wyćwiczona [A Well-trained Wife], Złote jarzmo małżeńskie [The Golden Yoke of Marriage], Corzka wolność młodzieńska [The Bitter Freedom of Youth] and Małpa-człowiek w cnotach, obyczajach i kroju [The Monkey in virtues, customs and clothes]. The suggested inter-genre division into satires and structures allows to see the ties which join Polish literature with European traditions, and at the same time takes into account their distinctness. The standard example of this is a form of a manippean letter (among others, often found in I. Krasicki's works), noted as an aftermath of menippea. The article fits within the current of philological studies on the menippean satire, which has been undertaken only recently.